Judges’ Role in Suspect Determination and Evolving Legal Concepts - Pujiyono Suwadi; Hasbullah , Hasbullah; Anurat Anantanatorn; Tojiboev Akbar Zafar Ogli (Jurnal Justice Dialectical, 2025)
Corruption is classified as an extraordinary crime, necessitating the adoption of non-traditional law enforcement strategies. Recent developments allow judges to determine guilt or innocence based on evidence presented in court. This study examines the legal implications of judicial involvement in corruption investigations, with a particular emphasis on the evolving role of the dominus litis, traditionally reserved for public prosecutors. The research further explores reinterpretations of the negatief wettelijk principle and the concept of criminal awareness. Employing a normative juridical methodology, the study reviews relevant statutes, legal doctrines, and case law to inform its analysis. The findings suggest that judicial identification of suspects may undermine the principle of dominus litis and lead to institutional conflict between prosecutors and judges. This practice alters the application of the negatief wettelijk principle by enabling judges to form legal opinions before formal investigations are conducted. Additionally, the understanding of criminal awareness has shifted towards a more interpretive judicial approach. It is therefore essential to establish clear and equitable regulations governing judicial authority in corruption cases to ensure fair trials, prevent abuse of power, and maintain the balance and independence of law enforcement institutions.